The Effect of Health Promotion of Common Cold Massage Skills on The Duration of Healing of ARI (Common Cold) in Toddlers - Laili Fajriyah; Reny Retnaningsih (Health and Technology Journal (HTechJ), 2026)
Acute respiratory infections (ARIs), particularly the common cold, account for 30–40% of toddler consultations in primary care settings in Indonesia. Nonpharmacological complementary therapies are urgently needed to reduce disease burden and antibiotic misuse. To evaluate the impact of a 2-day parent-administered "common-cold massage" program on illness duration among toddlers with mild ARI. A quasi-experimental, one-group pre-test/post-test study was conducted at PMB Nurul Asyaroti, Malang, Indonesia. Following ethical approval and parental consent, 16 toddlers (12–59 months) meeting the inclusion criteria were enrolled. Parents received a 30-minute health promotion session and an illustrated leaflet and then applied the 10-step massage twice daily for two consecutive days. Illness duration (in hours from baseline to the first 24-hour period free of nasal congestion/rhinorrhea) was documented by parents and verified by a blinded assessor on day 3. Data were analyzed with a paired t-test; effect size (Cohen's d) and 95% CI are reported. Mean illness-duration decreased from 4.6 days (SD 0.89) pre-intervention to 2.9 days (SD 0.62) post-intervention (mean reduction 1.7 days; 95 % CI 1.2–2.1; p < 0.001; Cohen's d = 2.1, indicating a huge effect). No adverse events were reported. Teaching parents a short, standardized massage significantly shortened the duration of common colds in toddlers. A randomized controlled trial is warranted to confirm the efficacy and cost-effectiveness of the intervention before scaling it across Indonesian community health centers.